2022
DOI: 10.1002/ajb2.1860
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic analyses in Phrymaceae reveal extensive gene tree discordance in relationships among major clades

Abstract: Premise: Phylogenomic datasets using genomes and transcriptomes provide rich opportunities beyond resolving bifurcating phylogenetic relationships. Monkeyflower (Phrymaceae) is a model system for evolutionary ecology. However, it lacks a wellsupported phylogeny as a basis for a stable taxonomy and for macroevolutionary comparisons. Methods: We sampled 24 genomes and transcriptomes in Phrymaceae and closely related families, including eight newly sequenced transcriptomes. We reconstructed the phylogeny using IQ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The section Simiolus and Erythranthe are phylogenetic sisters while Diplacus is the third outgroup (Beardsley and Olmstead 2002) and the three sections last shared a common ancestor 32-50 million years ago (Kumar et al 2017). Recent phylogenetic analyses indicate polyphyly of the genus Mimulus (Morales Briones et al 2022), and taxonomic revision has split these focal species into separate genera, Diplacus and Erythranthe (Barker et al 2012). However, following other recent work in the Phrymaceae, we have elected to retain the use of the name Mimulus for its historic significance and recognizability (see Lowry et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The section Simiolus and Erythranthe are phylogenetic sisters while Diplacus is the third outgroup (Beardsley and Olmstead 2002) and the three sections last shared a common ancestor 32-50 million years ago (Kumar et al 2017). Recent phylogenetic analyses indicate polyphyly of the genus Mimulus (Morales Briones et al 2022), and taxonomic revision has split these focal species into separate genera, Diplacus and Erythranthe (Barker et al 2012). However, following other recent work in the Phrymaceae, we have elected to retain the use of the name Mimulus for its historic significance and recognizability (see Lowry et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…(2023) infer a much later Cretaceous divergence time. We posit that the amount of (geological) time that elapsed since the Jurassic divergence we estimate from their MRCA, coupled with rapid, non-bifurcating diversification events (e.g., reticulation following polyploidy and hybridization; Morales-Briones et al., 2018 , 2021 , 2022 ) might have resulted in incomplete lineage sorting (ILS) in the nuclear compartment and might have obscured the order of relationships in the plastome, e.g., through plastid capture following hybrid speciation ( Folk et al., 2016 ; Liu et al, 2020 ; Yang et al, 2021b ). We argue that Eupteleaceae, which is part of the Arcto-Tertiary relict flora endemic to East Asia ( Cao et al., 2016 ), is indeed sister to all other ranunculalean families.…”
Section: Discussionmentioning
confidence: 99%
“…Although the two main biological sources of nuclear-plastid conflict, i.e. hybridization and ILS, have genomic signatures that are often difficult to discriminate ( Steenwyk et al., 2023 ; Stull et al, 2023 ), it is sometimes possible to differentiate between them ( Morales-Briones et al., 2018 , 2021 , 2022 ; Cai et al, 2021 ; Meleshko et al, 2021 ; McLay et al, 2023 ). In the case of Papaveraceae, it is possible to rule out allopolyploid hybridization as a potential cause of genomic discordances at nodes corresponding to floral symmetry transitions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have clarified relationships within several different clades, including the Boechera fendleri group (Alexander et al, 2015b), the Boechera suffrutescens group (Morin et al, 2018), and the Boechera puberula group (Schilling et al, 2018). Similar issues—backbone discordance and hybridization—have complicated phylogenetic resolution of other, similarly diverse ecological model systems such as Mimulus (Beardsley et al, 2004; Morales‐Briones et al, 2022) and Aquilegia (Fior et al, 2013) Two additional issues lend further complexity to phylogenetic resolution of Boechera : (1) the prevalence of polyploids (Schranz et al, 2005) and (2) the possibility of de novo evolution of sexual populations from rare recombination in facultatively asexual lineages (Carman et al, 2019), which would result in novel hybrid species like those found in other plant groups (e.g., Rieseberg et al, 2003). Newer methods have enabled robust resolution of Brassicaceae more broadly (Nikolov et al, 2019).…”
Section: Genus‐level Attributes Traits Of Primary Model Species Genus...mentioning
confidence: 99%